Relative sea-level stability and the radiocarbon marine reservoir correction at Natuna island, Indonesia, since 6400 yr BP - Wan, Jeannette Xiu Wen (2021)
A high-precision relative sea level (RSL) record over the past 6400 years, reconstructed from fossil coral microatoll colonies, is reported for Natuna Island, Indonesia. The timing of 11 fossil microatolls from four sites on Natuna Island is constrained by replicate 14C and 230Th dates. We investigate the local marine reservoir correction (∆R) using the replicate dates. The two sets of dates become aligned if a Marine20 ∆R of −143 ± 176 yr, 1σ (Marine13 ∆R of 15 ± 63 yr) is assigned to the 14C dates. The distribution of microatoll ages and elevations indicates that RSL was relatively stable from 6400 to 1400 yr BP at 0.2–0.7 ± 0.4 m (2σ) higher than present, before a fall to current levels. A comparison with the predictions of a suite of glacial isostatic adjustment (GIA) models for Southeast Asia suggests refinements are needed in ice-history models to fully capture our RSL data. These new constraints on past RSL of the Sunda Shelf contribute to further calibration of GIA models in the tropics, where RSL data are presently insufficient.